PENGGAMBARAN ETNIK BETAWI DALAM FILM BAJAJ BAJURI THE MOVIE - Fadillah Saleh; M. Sabrais (Universitas Mercu Buana, 2015)
Discourse on ethnic is an interisting thing to discuss, because there are a lot of ethnic in Indonesia, one of them is Betawi. In Indonesia, many movies and dramas which uses Betawi as a theme. One of the film with the theme of Betawi is Bajaj Bajuri The Movie. This is reflected in every scene and dialogue from Bajaj Bajuri The Movie. Issue that raised from this film is how the depiction of Betawi ethnic in Bajaj Bajuri The Movie and the purpose of this study is to determine how to Betawi ethnic depicted in Bajaj Bajuri The Movie.The type of research used in this research is descriptive qualitative approach- semiotic analysis. Analyst unit of this research in the from audio and video from Bajaj Bajuri The Movie.. The results showed that the Betawi ethnic has a wide range of culture and customs. Betawi ethnic depictions that looks on the Bajaj Bajuri The Movie is a Betawi woman with traditional clothes called Kebaya, and Betawi males with Jas Abang Jakarta and Sadariah clothes. There is also a Betawi arts like Tanjidor and Palang Pintu. This study concluded that Betawi ethnic has a wide range of cultures and traditions. Begin from clothing, traditional ceremonies, musical arts and martial arts. ethnic Betawi is indeed influenced by some of the ethnic in Indonesia and outside Indonesia. This is evident from the cultural or art that Betawi ethnic owned. Wacana tentang etnis adalah hal yang menarik untuk dibahas, karena ada banyak etnis di Indonesia, salah satunya adalah Betawi. Di Indonesia, banyak film dan drama yang menggunakan Betawi sebagai tema. Salah satu film dengan tema Betawi adalah Bajaj Bajuri The Movie. Hal ini tercermin dalam setiap adegan dan dialog dari Bajaj Bajuri The Movie. Isu yang diangkat dari film ini adalah bagaimana penggambaran Betawi etnis di Bajaj Bajuri The Movie dan tujuan dari penelitian ini adalah untuk menentukan bagaimana Betawi etnis digambarkan dalam Bajaj Bajuri The Movie.Jenis penelitian yang digunakan dalam penelitian ini adalah pendekatan deskriptif kualitatif -semiotik. Unit analis dari penelitian ini dalam dari audio dan video dari Bajaj Bajuri The Movie.. Hasil penelitian menunjukkan bahwa Betawi etnis memiliki berbagai macam budaya dan adat istiadat. penggambaran etnis Betawi yang terlihat pada Bajaj Bajuri The Movie adalah seorang wanita Betawi dengan pakaian tradisional yang disebut Kebaya, dan Betawi laki-laki dengan Jas Abang Jakarta dan Sadariah pakaian. Ada juga kesenian Betawi seperti Tanjidor dan Palang Pintu. Penelitian ini menyimpulkan bahwa etnis Betawi memiliki berbagai macam budaya dan tradisi. Mulai dari pakaian, upacara adat, seni musik dan seni bela diri. Betawi etnis memang dipengaruhi oleh beberapa etnis di Indonesia dan di luar Indonesia. Hal ini terlihat dari budaya atau seni yang dimiliki etnis Betawi.